Enhancement of interfacial adhesion in glass fiber/epoxy composites by electrophoretic deposition of graphene oxide on glass fibers. (1st April 2016) - Mahmood, Haroon; Tripathi, Manoj; Pugno, Nicola; Pegoretti, Alessandro
Abstract: Graphene oxide (GO) can increase the fiber/matrix interfacial shear strength (ISS) in glass fibers (GF) reinforced epoxy composites. To validate our argument, GO was synthesized and deposited over GF through electrophoretic deposition. Tuned voltage lead to different thickness of deposited GO steadily increasing with the electric field up to 10 V/cm. Coated fibers were aligned in a mold and an epoxy matrix was used to create a single-fiber microcomposite. Fragmentation test showed significantly higher ISS values for coated over bare fibers with increments up to a factor of about 2 and proportional to the amount of GO deposited on the GF. Tribological tests were performed at nanoscale by atomic force microscopy to measure the delamination strength between GO and GF. This latter resulted to be much higher than the ISS thus proving the efficiency of the new GO fiber coating method here proposed for producing advanced graphene based composites. The failure of the composite at the GO/matrix rather than at the GO/GF interface was also confirmed by scanning electron microscopy observation of the fracture surfaces of microcomposites.